CHALLENGES OF TRADITIONAL RULERS IN MAINTAINING PEACE AND HARMONY IN IDEATO NORTH LGA, IMO STATE, NIGERIA - Onyeiwu, Emmanuel Anayo (African Journal of Social and Behavioural Sciences, 2024)
This study focused on challenges of traditional rulers in maintaining peace and harmony in Ideato North LGA, Imo State, Nigeria. This study used the vacuum-filling theory to analyse the subject matter. The study employed a survey research design, and a questionnaire was used as the instrument for data collection. The data collected are presented in tables, and the data were analysed using simple percentages. The findings revealed that a lack of constitutional power/recognition affects traditional rulers in the maintenance of peace and harmony in the Ideato North LGA of Imo State, and a poor attitude of the people affects traditional rulers in the maintenance of peace and harmony in the Ideato North LGA of Imo State. It was recommended that traditional rulers be encouraged to mediate conflicts in society and should be educated and enlightened in modern and alternative dispute resolution to facilitate and enhance the resolution of conflicts in society. The study concluded that traditional rulers have put in place several measures in conflict resolution that have assisted in maintaining peace/harmony, law and order in their community.